2015
DOI: 10.1017/cem.2015.105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tamsulosin, Nifedipine, and Placebo for Ureteric Colic

Abstract: Clinical Question

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…For instance, infection with H. pylori was demonstrated to lead to gastritis and stomach cancer. 269,270 IBD was not sufficient to induce CRC in the absence of intestinal microbiota or microbial products, 271 and the use of a common antimicrobial additive Fig. 2 Inflammatory signaling pathways involved in cancer development.…”
Section: Cancer-promoting Inflammationmentioning
confidence: 99%
“…For instance, infection with H. pylori was demonstrated to lead to gastritis and stomach cancer. 269,270 IBD was not sufficient to induce CRC in the absence of intestinal microbiota or microbial products, 271 and the use of a common antimicrobial additive Fig. 2 Inflammatory signaling pathways involved in cancer development.…”
Section: Cancer-promoting Inflammationmentioning
confidence: 99%
“…21 However, Gottlieb and Nakitende recently performed a metaanalysis of tamsulosin, nifedipine, and placebo in treatment of ureteric colic; they found that combination tamsulosin and nifedipine therapy was not more effective than placebo in reducing the need for urologic intervention after 4 weeks of treatment among patients with acute ureteric colic. 12 Thus, additional clinical studies are needed to confirm the efficacy of nifedipine in treatment of ureteric stones.…”
Section: Discussionmentioning
confidence: 99%
“…10 Nifedipine continues to be used for clinical treatment of ureteral stones. 11,12 Several studies have shown that terazosin, an a-receptor antagonist for benign prostatic hyperplasia, 13 can be used to promote stone discharge in treatment of ureteral stones. 14,15 Moreover, terazosin is reportedly safe and effective in treatment of distal ureteral stones, especially stones >5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Seen in the broad context of all clinical trials of linagliptin, alogliptin, and sitagliptin, the increased HHF observed with saxagliptin in the SAVOR TIMI 53 trial is likely a compound-specific, rather than a general class effect ( Home, 2019 ). Conclusions about the class-specific effects of DPP4i should be done carefully, due to the structural variations of different DPP4i and the resulting differences in the selectivity toward DPP8 and DPP9 ( Riche and Davis, 2015 ). These differences may lead to altered adverse effect profiles which must be considered for each chemical entity.…”
Section: Dpp4 Inhibitors (Gliptins) In Cardiovascular Diseasementioning
confidence: 99%